Integrating Higher Order Thinking Skills (HOTS) into Literature-Based ESL Lessons - Mohamad Ali, Afiza (IIUM Press, 2024)
HOTS Integration In Literature with a Small 'l" Classroom: Benefit s, Challenges and Strategies